Match quality and house price dispersion: Evidence from Norwegian housing auctions - André Kallåk Anundsen; Arne Lyshol; Plamen T. Nenov; Erling Røed Larsen (Norges Bank, 2024)
Assessing the quantitative relevance of match quality and search frictions for house price dispersion is key to understanding house price formation and the importance of uninsurable housing wealth shocks. In this paper, we use a unique auction-level data set from Norway, combined with a structural model of the housing transaction process that includes frictional arrival and endogenous entry of buyers into bidding, as well as information frictions between buyers and sellers, to determine the importance of buyer taste heterogeneity for house prices and price dispersion. We find that quality differences matter greatly for house price dispersion, well beyond what hedonic pricing models may suggest, while buyer taste heterogeneity accounts for the majority of the remaining price dispersion. Our structural model implies that list prices often deviate substantially from seller valuations, lending support to theories of list price determination that feature strategic interactions between sellers/agents and buyers.
hdl:11250/3166747
Keywords: R21; R31; 330; structural estimation; search frictions; buyer-specific valuations; bidding wars; list price; selection effects; informational mismatch; overbidding